(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The psychosemantic role of Jungian Self Archetype in the Yu. Yanovsky’s novel in short stories «The Riders» is studied in the article. The author points out the importance of suicidal motives in the writer’s work as a formal and substantive factors of this archetype. The semantic contexts of using the image of Self in the text and the interpretation of its signification in Yu. Yanovsky’s prose are also analyzed.